Radiochemistry course in the undergraduate nuclear science program at Universiti Kebangsaan Malaysia - Sarmani, S. B.; Yahaya, R. B.; Yasir, M. S.; Majid, A. Ab; Khoo, K. S.; Rahman, I. A.; Mohamed, F. (Journal of radioanalytical and nuclear chemistry, 2015)
Universiti Kebangsaan Malaysia offered an undergraduate degree program in Nuclear Science since 1980 and the programme has undergone several modifications due to changes in national policy and priority. The programme covers nuclear sub-disciplines such as nuclear physic, radiobiology, radiochemistry, radiation chemistry and radiation safety. The radiochemistry component consists of radiochemistry, chemistry in nuclear industry, radiochemical analysis laboratory, radiopharmaceutical chemistry subjects and mini research project in radiochemistry.